The enhanced removal of phosphate by structural defects and competitive fluoride adsorption on cerium-based adsorbent. (October 2020) - He, Jiaojie; Xu, Yuhong; Xiong, Zhaokun; Lai, Bo; Sun, Yan; Yang, Yue; Yang, Liwei
Abstract: Trivalent cerium (Ce(Ⅲ)) was demonstrated to have great potential for phosphate (P) removal. Besides the valence states, the relationship of nano-structure and adsorption capacity needs further study to explore more efficient adsorbents. Herein, a series of Ce(Ⅲ)-terephthalate (BDC) metal-organic framework (MOF) with linker deficiencies are fabricated to achieve excellent P capture. The defective density can be increased by decreasing the reaction time and the ratio of organic linkers/metal. TGA reveals Ce-BDC-48 synthesized with BDC:Ce ratio of 1:1 for 48 h possessed 2.5 missing linkers per inorganic node. And the P uptake of Ce-BDC-48 was 35% higher than that of Ce-BDC-72 without defects. The maximum adsorption capacity of Ce-BDC-48 was 278.8 mg/g for P and 128.0 mg/g for fluoride (F), respectively. The adsorption mechanism illustrates that both P and F mainly focus on the Ce(Ⅲ) active sites to achieve ligand exchange. The competing adsorption of P and F at the lower concentration of F (50 mg/L) indicates that the interference of F for P removal is insignificant on account of the selective preferential order of P. However, with the increment of F concentration (100 mg/L), amount of F with small sizes gathering around the adsorbent surface enlarge the steric hindrance to hinder the access of P, leading to the sharp decline of P uptake. This study not only provides promising candidate by the design of structural defects for the P removal in practical application but also give a deep analysis on the adsorption mechanism of P with competing F surrounded. Graphical abstract: Image 1 Highlights: Ce-BDC-48 with linker deficiencies was fabricated by solvothermal reaction. The P uptake of Ce-BDC-48 was 35% higher than that of Ce-BDC-72 without defects. The maximum adsorption capacity of Ce-BDC-48 was 278.8 mg/g for P and 128.0 mg/g for F. Both P and F mainly competed for the Ce(Ⅲ) active sites to achieve ligand exchange. The higher concentration of F (100 mg/L) showed significant interference in P removal.